False lumen patency status and outcomes after endovascular repair of uncomplicated chronic type B dissection. Issue 4 (13th September 2022) - Kong, Minjian; Ni, Ming; Zhu, Xian; Qian, Jianfang; Duan, Qunjun; Song, Jiangwei; Feng, Zhanzeng; Dong, Aiqiang
Abstract: Background: Thoracic endovascular aortic repair (TEVAR) remains a controversial treatment for uncomplicated chronic type B aortic dissection (cTBAD). This study was performed to investigate the postoperative outcomes of TEVAR, such as survival and reintervention, and the risk factors for prognoses. Methods: In total, 41 patients with uncomplicated cTBAD who underwent TEVAR from 2014 to 2021 were reviewed. The patients were divided into two groups: those with false lumen complete thrombosis (FLCT) and false lumen partial thrombosis (FLPT) based on computed tomography angiography (CTA) images. Kaplan–Meier analysis was performed to estimate survival and freedom from reintervention. Binary logistic analysis was performed to estimate risk factors for partial thrombosis. Results: During a mean follow‐up of 31 (1–78) months, five deaths and six reinterventions had occurred at 5 years. By 1 week, thoracic FLCT had occurred in 23 (56.1%) patients and thoracic FLPT had occurred in 18 (43.9%). The rate of freedom from reintervention was significantly lower in the FLCT than in the FLPT group ( p = 0.04). The 5‐year survival rate of the two groups was not statistically significant ( p = 0.14). Risk factors for thoracic FLPT were the distance between the re‐entry site and the graft ( p = 0.02) and the proximal oversizing ratio ( p = 0.04). Conclusions: TEVAR is an effective and safe treatment for uncomplicated cTBAD and has a low mortality rate. Thoracic FLCT is associated with less reintervention, but overall survival is not impacted by this difference. Patients treated with TEVAR without certain risk factors can have a good prognosis.